Searching for 'community' and 'community involvement' in urban policy. Issue 4 (2nd October 2018) - Kyung, Shinwon
ABSTRACT: The idea of 'community involvement' has regained its importance in many parts of the world. However the meaning and application of community involvement are still not considered to be clearly defined. This lack of clarity often leads to contradictions and it prevents governments from providing clear policy purpose. This paper, therefore, starts by searching for the idea of community and community involvement and how it is interpreted in different cultural contexts. It then moves to explore different approaches towards, and models of, community involvement in urban policy including the current debates on their strengths and weaknesses. In the conclusion, this paper discusses the gap between academic inquiry and development practice in the real world.